EDUCAÇÃO AMBIENTAL EM UM CURSO DE EDUCAÇÃO PROFISSIONAL TÉCNICA DE NÍVEL MÉDIO. ESTUDO DE CASO EM UMA INSTITUIÇÃO FEDERAL DE ENSINO - Castilho, Priscila da Silva (2013)
Amid a backdrop of degradation environmental degradation, it is deemed to reflect on environmental issues you need to think about the survival of humans. In this context, sustainability is an issue debated by various civil society groups because they understand that it is an important part of the process of struggle for the maintenance of human existence. In this sense, environmental education plays a crucial role in the formation of subjects capable of intervening in society towards its transformation process. Despite the understanding that there are about education being key to form citizens who aspire to a sustainable society and seek, much has been advancing the field of education. Given the above, the Survey aims to analyze the perceptions of teachers, who work in a Course of Technical Education Middle Level, offered by a Federal Institution, of Education on Environmental Education. Furthermore, we sought to determine if this education happens in the course studied. The methodology of research we used the single case study. To achieve the goal outlined, held, bibliographic through bibliometric study and semi-structured questionnaire applied to teachers surveyed. The results show that more than half of the participants considered it essential to the development of Environmental Education Technical Education Middle Level. Nevertheless, the results also demonstrate that none of the respondents agree that environmental education is part of the course curriculum researched, as current law provides.